Ethical codes expected of school administrators - Demirtas, Zulfu (Academic Journals, 2010)
The aim of this study was to evaluate ethical codes used by school administrators in Turkey. The study assessed the perceptions and doubts of school administrators about the ethical codes they are expected to obey. The study used the qualitative research model. The study group was comprised of school administrators working in primary schools and high schools in Elazig and Sanliurfa provinces of Turkey during the 2008 - 2009 academic years. The participants reported/developed a total of 34 codes. Among these codes, the highest recognition occurred in the justice and honesty ethical codes. These two ethical codes are followed by the professional competence and objectivity codes respectively. Fourteen of the developed ethical codes were developed/reported by only one participant.
Keywords: Ethics; ethical codes; professional ethical codes; school administrators; school administrator's ethical codes